2022
DOI: 10.3390/ijms23137271
|View full text |Cite
|
Sign up to set email alerts
|

Y192 within the SH2 Domain of Lck Regulates TCR Signaling Downstream of PLC-γ1 and Thymic Selection

Abstract: Signaling via the TCR, which is initiated by the Src-family tyrosine kinase Lck, is crucial for the determination of cell fates in the thymus. Because of its pivotal role, ablation of Lck results in a profound block of T-cell development. Here, we show that, in addition to its well-known function in the initiation of TCR signaling, Lck also acts at a more downstream level. This novel function of Lck is determined by the tyrosine residue (Y192) located in its SH2 domain. Thymocytes from knock-in mice expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Phosphorylation of Y192, Y394 (as detected by the anti-pSrcY416 antibody) and Y505 were undetectable in Jk.LCKKO cells expressing LCKmut after anti-CD3 stimulation (Fig. 5 a) [ 33 ]. As expected, global tyrosine phosphorylation was strongly reduced in control Jk.LCKKO cells and cells expressing LCKmut, but reconstituted after re-expression of LCKwt as detected by developing with the 4G10 antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of Y192, Y394 (as detected by the anti-pSrcY416 antibody) and Y505 were undetectable in Jk.LCKKO cells expressing LCKmut after anti-CD3 stimulation (Fig. 5 a) [ 33 ]. As expected, global tyrosine phosphorylation was strongly reduced in control Jk.LCKKO cells and cells expressing LCKmut, but reconstituted after re-expression of LCKwt as detected by developing with the 4G10 antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This potential interaction with ZAP70 was however not associated with a detectable anti-CD3-induced phosphorylation at Y192 [ 26 ] in LCKmut(S377KTer14) in our transfection system. Phosphorylation of Y192 is relevant for the co-localization of LCK with CD45 and the TCR [ 26 , 33 ]; thus, the lack of phosphorylation may contribute to the observed aberrant subcellular localization of the truncated protein despite an intact N-terminus domain anchoring LCK to the plasma membrane in the truncated LCKmut [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the phosphorylation of Y192 diminishes the interaction between Lck and its positive regulatory phosphatase CD45, thus resulting in the hyper-phosphorylation of Y505 in Lck and in its inactivation [ 14 ]. Conversely, we have shown that a phosphomimetic Lck Y192E mutant still retains its enzymatic activity and is able to initiate signaling in thymocytes [ 15 , 22 ], highlighting that the initial steps of TCR activation and signal propagation are not fully understood. In this study, we revealed a new feedback loop involving Lck and Zap70.…”
Section: Discussionmentioning
confidence: 99%
“…This is an unusual regulatory mechanism by which a phosphorylation event triggers the uncoupling of two proteins, and this should be the reason why the mutation to phenylalanine of tyrosine 192 does not have a negative impact on TCR signaling: Phe residues could be structurally not so different from Tyr residues, and are still able to bind to CD45, while Tyr to Ala or Glu induces a strong modification of the tertiary structure of the SH2 domain, preventing binding to CD45 and thus leading to a high basal level of Tyr505 phosphorylation, which sharply reduces the pool of active Lck. Accordingly, knockin mice expressing a Tyr to Glu (Y192E) form of Lck showed a strong decrease in the total thymocyte numbers, with reduced numbers of DP and SP populations and defective positive and negative selection [ 99 , 100 ]. Interestingly, T cells from LckY192E knockin mice showed a diminished binding to CD45 and a concomitant hyperphosphorylation of Y505, thus corroborating previous data obtained from Jurkat T cells.…”
Section: Regulation Of Lck Activitymentioning
confidence: 99%